Antibiotic prescribing amongst South African general practitioners in private practice: an analysis of a health insurance database. Issue 5 (30th September 2022) - Alabi, Mobolaji Eniola; Essack, Sabiha Yusuf
Abstract: Objectives: To investigate the appropriateness of antibiotic prescribing among GPs in the private primary healthcare sector in South Africa. Methods: An anonymized national database of claims for antibiotic prescriptions was obtained from a large medical insurer. Antibiotic prescriptions were categorized based on International Classification of Diseases (ICD-10) codes as 'appropriate', 'potentially appropriate' and 'inappropriate' using a classification scheme developed by Chua et al. ( BMJ 2019; 364: k5092). Further assessments of antibiotic choice, dosage and duration of treatment were carried out to determine the appropriateness of 'appropriate' and 'potentially appropriate' prescriptions in comparison with treatment guidelines. Results: In February 2018, 188 141 antibiotics were prescribed for 174 889 patients who consulted GPs in the private sector. Penicillins were the most frequently prescribed antibiotic class, making up 40.7% of all antibiotics prescribed. Amoxicillin/clavulanic acid was the most frequently prescribed antibiotic, making up 28.6% of all antibiotics prescribed. Diseases of the respiratory system generated the highest number of prescriptions, making up 46.1% of all diagnoses. Of all prescriptions, 8.8% were appropriate, 32.0% were potentially appropriate, 45.4% were inappropriate and 13.8% could not be assessed. Of the appropriately and potentially appropriately prescribed antibiotics, 30.8% were correct antibiotic selections. Of the correctly selected antibiotics for adults, 57.7% had correct doses. Of the antibiotics prescribed with correct doses for adults, 76.7% had correct dosage frequencies and durations of treatment. Conclusions: The study revealed that antibiotics were frequently prescribed inappropriately by GPs in the private primary healthcare sector. There is thus a need to develop stewardship interventions in the sector.